Free energy perturbation in the design of EED ligands as inhibitors of polycomb repressive complex 2 (PRC2) methyltransferase. (1st May 2021) - O' Donovan, Daniel H.; Gregson, Clare; Packer, Martin J.; Greenwood, Ryan; Pike, Kurt G.; Kawatkar, Sameer; Bloecher, Andrew; Robinson, James; Read, Jon; Code, Erin; Hsu, Jessie Hao-Ru; Shen, Minhui; et al.
Graphical abstract: Highlights: A series of triazolopyrimidine EED ligands is reported which explores a novel pocket within the binding site. Free Energy Perturbation (FEP) calculations were used to predict their affinity, as verified by surface plasmon resonance (SPR) A synthetic approach incorporating late-stage functionalization (LSF) enabled rapid exploration of SAR. New ligands retain high affinity for EED while improving their physicochemical properties. Abstract: Free Energy Perturbation (FEP) calculations can provide high-confidence predictions of the interaction strength between a ligand and its protein target. We sought to explore a series of triazolopyrimidines which bind to the EED subunit of the PRC2 complex as potential anticancer therapeutics, using FEP calculations to inform compound design. Combining FEP predictions with a late-stage functionalisation (LSF) inspired synthetic approach allowed us to rapidly evaluate structural modifications in a previously unexplored region of the EED binding site. This approach generated a series of novel triazolopyrimidine EED ligands with improved physicochemical properties and which inhibit PRC2 methyltransferase activity in a cancer-relevant G401 cell line.